Protein Fortification in Melarat Crackers with Protein Hidrolyzate Flour of Tilapia (Oreochromis niloticus) Meat - Junianto Junianto; Alexander M.A. Khan; Iis Rostini (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
Melarat crackers is typical crackers in the Priangan area, West Java that rich in carbohydrate but poor in protein. The purpose of this study was to determine the level of addition of tilapia meat protein hydrolyzateflour which is appropriate in the manufacture of melarat crackers to produce the most preferred product, to determine the chemical composition and the level of cracking of the preferred product. The method used was an experimental study using a completely randomized design of four treatments and repeated 4 times. The four treatments were 0%, 5%, 10% and 15% levels of addition of flour protein tilapia hydrolyzate from tapioca flour used. The parameters observed included the chemical composition, the level of organoleptic preferences and the cracking level of melarat crackers resulting from the various treatments. The results showed that melarat cracker with the addition of 10% tilapia protein hydrolyzate flour was the most preferred by panelists. The content of water, protein, fat, ash and carbohydrates of these melarat crackers was 5.99%; 5.50%; 0.12%; 5.63%; and 82.79%. The level of cracking was 55.3%.